Selective removal of uranium ions from contaminated waters using modified-X nanozeolite. (December 2016) - Shakur, H.R.; Rezaee Ebrahim Saraee, Kh.; Abdi, M.R.; Azimi, G.
Abstract: In order to efficiently remove of uranium anionic species (which are the most dominant species of uranium in natural water at neutral pH) from contaminated waters, nano-NaX zeolite was synthesized and then modified using various divalent cations (Mg 2+, Ca 2+, Mn 2+ ) and ZnO nanoparticles (from 1.7 to 10.3 wt%). Different characterization techniques of XRF, XRD, FE-SEM, TEM, FT-IR, and AAS were used to characterize the final synthesized absorbents. Sorption experiments by batch technique were done to study the effect of solid-liquid ratio, initial uranium concentration, contact time and temperature under neutral condition of pH and presence of all anions and cations which are available in the waters. Results showed that although nano-NaX zeolite due to its negative framework charge had a low sorption capacity for adsorption of uranium anionic species, but modification of parent nano-NaX zeolite with ZnO nanoparticles and various cations effectively improved its uranium adsorption capacity. Also, results showed that under optimum condition of pH=7.56, contact time of 60 min at 27 °C with solid-liquid ratio of 20 g/L a maximum uranium removal efficiency of 99.7% can be obtained in the presence of all anions and cations which are available in the drinking waters by NaX/ZnO nanocomposite. Highlights: Synthesized X nanozeolite modified by a cation exchange process and ZnO nanoparticle. Removal of uranium anionic species from water with high efficiency and selectivity. Removal of uranium anions in the presence of all anions and cations existing in the water. Increase in sorption capacity by increasing ZnO wt% on NaX nanozeolite. Increase in sorption capacity by increasing the charge/radius ratio of exchanged cation.